Hadith Ahkam and the Qualifications for Fiqh Development - Saleh, Fauzi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
Hadith Ahkam has historically received insufficient attention in the development of Islamic law, despite its critical role as the second primary source after the Quran. This qualitative study employs an Ulumul Hadith approach and utilizes documentation methods. The findings reveal, first, that Hadith Ahkam comprises the sayings, actions, and tacit approvals of the Prophet Muhammad (PBUH) with legal implications. Hadith Ahkam plays a significant role in the development of Islamic law, covering various aspects such as worship (ibadah), transactions (muamalah), and marriage (munakahah). Therefore, there is a need for a more representative understanding methodology to address contemporary issues from the perspective of the Sunnah of the Prophet. Second, the qualifications of a mujtahid in developing fiqh related to ahkam include proficiency in the Arabic language, understanding of Fiqh and Usul Fiqh, knowledge of Ilm Mukhtalaf al-Hadith, and awareness of classical and contemporary scholarly developments.